New case of syncytial giant-cell variant of hepatocellular carcinoma in a pediatric patient with HNF1B deficiency: does it fit with the syndrome? - Michele Pinon; Pier Luigi Calvo; Davide Tinti; Silvia Kalantari; Luca Fabris; Massimiliano Cadamuro; Alessandro Gambella; Renato Romagnoli; Laura Giugliano; Cristina Chiadò; Valeria Bracciamà; Silvia Deaglio; et al. (BMJ Open Gastroenterology, 2022)
Background Hepatocyte nuclear factor 1B (HNF1B) is a member of the homeodomain-containing family of transcription factors located on 17q12. HNF1B deficiency is associated with a clinical syndrome (kidney and urogenital malformations, maturity-onset diabetes of the young, exocrine pancreatic insufficiency) and to an underdiagnosed liver involvement. Differently from HNF1A, the correlation between hepatocellular carcinoma (HCC) and germline HNF1B deficiency has been poorly evaluated.Case report Here, we report a novel case of a syndromic HNF1B-deficient paediatric patient that developed HCC with unique histopathological features characterised by neoplastic syncytial giant cells, which was observed only in one additional case of paediatric cholestatic liver disease of unknown origin.Conclusions Our case highlights the influence of HNF1B deficiency in liver disease progression and its putative association with a rare yet specific HCC histotype. We hypothesised that HCC could be secondary to the repressive effect of HNF1B variant on the HNF1A transcriptional activity.